Los préstamos otorgados por el sistema financiero y el empleo en Loreto periodo 2018 – 2022 - Macha Tamani, José Roberto (2025)
Credit and labor are two productive factors directly related to the evolution of the economy, measured through the Gross Domestic Product (GDP). The objective proposed in this master's thesis is to determine the relationship between the loans granted by the financial system and employment in Loreto, in the period 2018 - 2022. In this desire for study, this research of a Quantitative and Correlational nature is prepared. according to the level of explanation; The design is Non-Experimental. The conclusions resulting from the research are: there is no direct relationship between the loans granted by the financial system and employment in Loreto, during the period 2018 - 2022, because the Correlation Coefficient was r = 0.235639822; and the Coefficient of Determination R2 = 0.055526126; very far from the minimum required values. Likewise, the highest value of the loans granted corresponds to Commercial Banking (62.50%). The delinquency of the Commercial Bank (9.00%) is above the delinquency of the financial system (7.96%); However, the entity with the highest reported delinquency is the Agrobanco (91.62%), an entity with little weighted weight in the system. In the same order of things, the occupation category that had the largest mass of workers in it was Independent Worker (50.11%), the same one that is strongly linked to the informal sector of the economy.